International Tax Coordination: Regionalism versus Globalism - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
Tax competition for mobile capital can undermine the attempts of governments to redistribute income from rich to poor. I study whether international tax coordination can alleviate this problem, using a general equilibrium model synthesizing recent contributions to the tax competition literature. The model highlights the crucial distinction between global tax coordination and regional coordination. With high capital mobility between the tax union and the rest of the world, the welfare gain from regional capital income tax coordination is only a small fraction of the gain from global coordination, even if the tax union is large relative to the world economy.
Keywords: 330